p53 contributes to T cell homeostasis through the induction of pro-apoptotic SAP - Madapura, Harsha S. (Landes Bioscience, 2012)
Lack of functional SAP protein, due to gene deletion or mutation, is the cause of X-linked lymphoproliferative disease (XLP), characterized by functionally impaired T and NK cells and a high risk of lymphoma development. We have demonstrated earlier that SAP has a pro-apoptotic function in T and B cells. Deficiency of this function might contribute to the pathogenesis of XLP. We have also shown that SAP is a target of p53 in B cell lines. In the present study, we show that activated primary T cells express p53, which induces SAP expression. p53 is functional as a transcription factor in activated T cells and induces the expression of p21, PUMA and MDM2. PARP cleavage in the late phase of activation indicates that T cells expressing high levels of SAP undergo apoptosis. Modifying p53 levels using Nutlin-3, which specifically dissociates the MDM2-p53 interaction, was sufficient to upregulate SAP expression, indicating that SAP is a target of p53 in T cells. We also demonstrated p53’s role as a transcription factor for SAP in activated T cells by ChIP assays. Our result suggests that p53 contributes to T cell homeostasis through the induction of the pro-apoptotic SAP. A high level of SAP is necessary for the activation-induced cell death that is pivotal in termination of the T cell response.